Transpedicular drainage of Pott's abscess. A report of two cases - (:unkn) unknown (My University, 1995)
The treatment of Pott's disease remains controversial. The authors present two cases of spinal tuberculosis treated with posterior stabilization and supplementary abscess evacuation via the pedicular route with subsequent chemotherapy. The aim of this procedure was to increase the healing rate. Radiographic evidence of bone healing without any sequelae was demonstrated at 13 and 14 months.
Keywords: Adult; Female; Humans; Middle Aged; Tomography, X-Ray Computed; Male; Magnetic Resonance Imaging; Curettage; Internal Fixators; Tuberculosis, Spinal; Abscess